Valorization of textile waste hydrolysate for hydrogen gas and levulinic acid production - Özsel Kaya, Burçak (Pergamon-Elsevier Science Ltd, 2021)
The objective of this research was to explore the potential for utilizing cellulose-based waste fluff that constitute a significant portion of the solid waste of textile industry to obtain high yield hydrogen gas and levulinic acid by using two-step conversion process. In the first step, hydrothermally hydrolysis of cellulose-based waste fluff was achieved and then the hydrolysate solution was further treated by two different catalysts (Pt/AC and BT500S) in different reaction conditions for producing hydrogen gas and levulinic acid. The results showed that in reforming process the highest gasification performance and hydrogen selectivity (increased up to 25.6%) were achieved from waste fluff hydrolysate compared to other lignocellulosic/cellulosic hydrolysates studied in the literature. On the other hand, 655.3 mg/mL hydrolysate of levulinic acid was produced at the reaction temperature of 200 degrees C with BT500S solid acid catalyst corresponding to a higher concentration than during one-step conversion process. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Textile waste; Hydrogen; Levulinic acid; Two-step conversion process